Reluctant sleuths, true detectives - Jacobs, Jason (State University of New York Press, 2023)
Explores the figure of the detective as a pursuer of knowledge in four noir films.
Keywords: Out of the past (Motion picture : 1947); Notorious (Motion picture : 1946); Vertigo (Motion picture : 1958); Chinatown (Motion picture); Detective and mystery films -- United States -- History and criticism.; Film noir -- United States -- History and criticism.; Knowledge, Theory of, in motion pictures.; Motion pictures -- Philosophy.; Films de détective -- États-Unis -- Histoire et critique.; Films noirs -- États-Unis -- Histoire et critique.; Théorie de la connaissance au cinéma.; Cinéma -- Philosophie.; PERFORMING ARTS / Film & Video / History & Criticism.; Detective and mystery films; Film noir; Knowledge, Theory of, in motion pictures; Motion pictures -- Philosophy; United States; Electronic books.; Criticism, interpretation, etc.